Mirror-enhanced scanning light-field microscopy for long-term high-speed 3D imaging with isotropic resolution - Bo Xiong (Nature Publishing Group, 2021)
Mirror-enhanced scanning light-field microscopy (MiSLFM) achieves long-term high-speed 3D imaging at near-isotropic subcellular resolution with a single objective, facilitating native observations of various intracellular and intercellular interactions.